(untitled) (TAMADDUN NURI JURNALI, 2025)
This article analyzes the legal and theoretical-methodical foundations of the reforms implemented in the years of independence of the Republic of Uzbekistan from 1991 to the present. The main directions of the reforms, their reliance on the Constitution and legislative framework, as well as the role of theoretical concepts and methodological approaches are studied. The article evaluates the effectiveness of the reforms based on statistical data and examples and makes suggestions for future prospects. The research used historical, analytical and comparative methods